INTEGRATION OF INFORMATION COMPUTER TECHNOLOGIES OF QUALITY MANAGEMENT SYSTEM: AUTOMATION OF MARKING PROCEDURE - S. A. Pavlenko (Литьë и металлургия, 2012)
Integration of IT with concept elements “Poka-jeke” in quality system allows to lower variability of processes and to receive effective results at control of product quality.